Effect of workshop education model based on Omaha system on compliance behavior of patients undergoing endoscopic lumbar discectomy for lumbar disc herniation (基于奥马哈系统的工作坊宣教模式对腰椎内镜技术治疗腰椎间盘突出症患者遵医行为的影响) - HE Shuiwen (何水文); YU Yuxiu (于玉秀); OU Jinshi (欧金石); TANG Qin (唐琴) (Association of Integrative Nursing, 2023)
Objective To explore the application of workshop education model based on Omaha system in the perioperative nursing of patients undergoing endoscopic lumbar discectomy for lumbar disc herniation, and evaluate its effect on compliance behavior of patients. Methods A convenience sample of 120 patients who underwent with endoscopic lumbar discectomy for lumbar disc herniation were included and divided into the control group. Based on the routine orthopedic care bundles, the control group received routine health education during hospitalization, and the observation group received workshop education mode based on Omaha system. The patient compliance, rehabilitation outcome and satisfaction was evaluated by compliance behavior and LDG-Knowledge questionnaire, Japanese Orthopaedic Association (JOA) scale and self-made satisfaction questionnaire, respectively. Results There was 1 case of death and 3 cases lost to follow-up, and clinical data of 57 cases in the control group and 59 cased in the observation group were analyzed. Scores of compliance behavior and LDG-Knowledge questionnaire in the observation group were higher than those in the control group at discharge form hospital, 1 month and 3 months after discharge from hospital respectively (P<0. 01). Patients in the observation group achieved higher JOA scores compared with those in the control group at discharge form hospital, 1 month and 3 months after discharge from hospital respectively (P<0. 01). The satisfaction score in the observation group was higher than that in the control group at discharge form hospital (P<0. 05). Conclusion The workshop education model based on Omaha system is potentially effective to improve the compliance behavior of patients after endoscopic lumbar discectomy and promote postoperative rehabilitation. (目的 探讨基于奥马哈系统的工作坊宣教模式在腰椎间盘突出症患者内镜手术治疗围手术期护理中的应用效果, 探讨其对患者术后遵医行为的影响。方法 采用便利抽样法选取2021年1月-2022年3月120例腰椎间盘突出症患者为研究对象, 均接受腰椎内镜手术治疗。在常规专科护理基础上, 对照组采用常规住院宣教模式, 干预组采用基于奥马哈系统的工作坊宣教模式进行宣教。采用遵医行为和腰椎间盘突出症知识调查问卷评估患者遵医行为, 采用日本骨科协会评分系统(JOA)评价康复效果, 采用自制量表评价患者满意度。结果 随访中死亡1例、失访3例。对照组57例和干预组59例纳入最终研究。出院时、出院1个月、出院3个月, 干预组遵医行为和腰椎间盘知识问卷评分高于对照组, 差异有统计学意义(P<0. 01); 干预组JOA评分高于对照组, 差异有统计学意义(P<0. 01)。出院时干预组满意度评分高于对照组, 差异有统计学意义(P<0. 01)。结论 基于奥马哈系统的工作坊宣教模式有利于促进腰椎间盘突出症患者腰椎内镜术后遵医行为, 从而促进康复。)